'First and foremost a writer of fiction': revisiting two Toronto novels, Hopkins Moorhouse's Every Man for Himself and Peter Donovan's Late Spring. Issue 2 (September 2015) - Smith, Will
Abstract : Hopkins Moorhouse and Peter Donovan (or P.O'D.) were once familiar names in Canadian literature. In the first decades of the twentieth century both authors wrote a variety of sketches and stories for Canadian magazines and newspapers, and went on to produce well-received, popular, Toronto-set novels. The intervening years have seen both writers and their novels all but forgotten. This article revisits Moorhouse's Every Man for Himself (1920) and Donovan's Late Spring (1930) in light of an increasing interest in the depiction of cities in Canadian literature. Both novels can be seen as self-aware modern urban Canadian fictions, addressing the complexity of the cityscape alongside the overarching challenges of modernity to literary representation.